2020
DOI: 10.3390/ma13020395
|View full text |Cite
|
Sign up to set email alerts
|

Powder-in-Tube Reactive Molten-Core Fabrication of Glass-Clad BaO-TiO2-SiO2 Glass–Ceramic Fibers

Abstract: In this paper we report the fabrication of glass-clad BaO-TiO2-SiO2 (BTS) glass–ceramic fibers by powder-in-tube reactive molten-core drawing and successive isothermal heat treatment. Upon drawing, the inserted raw powder materials in the fused silica tubing melt and react with the fused silica tubing (housing tubing) via dissolution and diffusion interactions. During the drawing process, the fused silica tubing not only serves as a reactive crucible, but also as a fiber cladding layer. The formation of the BT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…Moreover, the positions of these peaks are red shifted with varying compositions of the samples BZTS0C, BZTS2C, BZTS4C, and BZTS6C respectively [18]. It is reported that the transmittance bands in oxide spectra are usually arisen owing to the grouping of high degeneracy vibrational states, and thermal broadening of the lattice dispersion bands from the powdered glass samples [47]. In the low wavenumber range, two distinct modes, i.e.…”
Section: Density and Molar Volume Analysis Of Glass And Glass Ceramicsmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, the positions of these peaks are red shifted with varying compositions of the samples BZTS0C, BZTS2C, BZTS4C, and BZTS6C respectively [18]. It is reported that the transmittance bands in oxide spectra are usually arisen owing to the grouping of high degeneracy vibrational states, and thermal broadening of the lattice dispersion bands from the powdered glass samples [47]. In the low wavenumber range, two distinct modes, i.e.…”
Section: Density and Molar Volume Analysis Of Glass And Glass Ceramicsmentioning
confidence: 98%
“…More recently, BaO-TiO 2 -SiO 2 based glasses were synthesized using the powder-intube reactive molten-core technique for photoluminescence applications. Furthermore, this technique provides more efficient and impurity free process to design and fabricate the glass ceramic fibers [47]. Herein, the main focus was taken in to account to synthesize the lead-free glass and glass ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…Although the origins of transparent active GC doped with lanthanide ions date back to the 1970s [ 17 ] and optical fibers’ the 1960s [ 11 , 18 ], GC still poses problems when drawing optical fibers. Glass-ceramics compromise quantum efficiency [ 19 , 20 , 21 ], which depends on the local environment around RE ions, the chemical composition, luminescence, and thermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the melting and, after that, the drawing process, degrades crystals [ 19 , 25 ]. Alternatively, the core material can be melted inside the cladding material, and this method is melt-in-tube (molten-core) or powder-in-tube [ 10 , 18 , 26 , 27 ]. This method of obtaining fibers involves diffusion problems between core and cladding materials, core irregularity and the difference between core and cladding in melting point, and viscosity [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation